ByzRev 07.2025.062: Markéta Kulhánková, Cease Writing of Achilles: A Narratological Commentary on the Byzantine Heroic Poem Digenis Akritis: (Mnemosyne Supplements 494). Leiden – Boston: Brill 2025. - Ghidoni, Andrea (The Byzantine Review, 2025)
Markéta Kulhánková, Cease Writing of Achilles: A Narratological Commentary on the Byzantine Heroic Poem Digenis Akritis (Mnemosyne Supplements 494). Leiden – Boston: Brill 2025. x+261 pp. – ISBN 978-90-04-73311-4